REKONSILIASI SAINS ISLAM KONSEP, PRINSIP, DAN IMPLEMENTASI HUMANISASI ILMU - Ainidian Saputri, Aini; Irmasari , Nur Aini; Fadlan Ramadan, Muhammad; Prayogi, Arditya (Najah Bestari, 2026)
This research is motivated by the perceived contradiction between the values of modern scientific knowledge and Islamic religious studies. The objective is to deepen and formulate the Reconciliation of Islamic Science through the concept of the Humanization of Knowledge. This study employs a conceptual literature review method by analyzing relevant written sources. The results indicate that the Reconciliation of Islamic Science is realized through a comprehensive understanding of the Humanization of Knowledge, which is characterized by three main principles: the utilization of knowledge in understanding religious teachings, the relevance of religious teachings to social problems, and the internalization of the substance of teachings into the human personality. The implementation of the Humanization of Knowledge affirms the integration of the vertical dimension (relationship with God) and the horizontal dimension (relationship with fellow humans) in the development of science. It can be concluded that the Humanization of Knowledge offers a strong framework for aligning science and Islam by placing humanitarian and spiritual values at the core of the entire scholarly process.